2018
DOI: 10.21829/abm126.2019.1369
|View full text |Cite
|
Sign up to set email alerts
|

Diversidad de arbustos a lo largo de gradientes de elevación y perturbación en el centro de Veracruz, México

Abstract: Antecedentes y Objetivos: Los arbustos son un elemento florístico importante de los bosques tropicales; sin embargo, la investigación sobre plantas con esta forma de crecimiento aún es escasa. El objetivo principal de este estudio consistió en analizar la influencia de la elevación y la perturbación en los patrones de distribución y diversidad de los arbustos en la región central de Veracruz, México.Métodos: Se estableció un gradiente elevacional (20-3500 m s.n.m) en la ladera este del Cofre de Perote, donde s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
0
5
0
2
Order By: Relevance
“…Abiotic variables related to elevation (such as temperature, precipitation, and productivity) have a direct influence on species diversity in Neotropics (Rahbek, 1995). Especially in our study area, it has been shown that there is a different effect of this variable on different plant groups (Bautista-Bello et al, 2019; Monge-González et al, 2020). Mainly, this pattern could be explained by the interactive effect of temperature and water availability known as the water-energy dynamics hypothesis (O’Brien, 1998).…”
Section: Discussionmentioning
confidence: 65%
“…Abiotic variables related to elevation (such as temperature, precipitation, and productivity) have a direct influence on species diversity in Neotropics (Rahbek, 1995). Especially in our study area, it has been shown that there is a different effect of this variable on different plant groups (Bautista-Bello et al, 2019; Monge-González et al, 2020). Mainly, this pattern could be explained by the interactive effect of temperature and water availability known as the water-energy dynamics hypothesis (O’Brien, 1998).…”
Section: Discussionmentioning
confidence: 65%
“…This pattern for herbs may be shaped by human disturbances and length of the growing season, which may have a more pronounced influence on the persistence and growth of short-living (annual and biennial) herbs than on that of perennial woody plants (Gómez-Díaz et al, 2017;Bhatta et al, 2021). The slightly increasing contribution of shrubs to total richness along the elevation gradient may be shaped by the interaction among PET, anthropogenic disturbance, and temperature change along the elevation gradient, as reported in Veracruz, Mexico (Bautista-Bello et al, 2019) and northern China (Zhang et al, 2016).…”
Section: Contribution Of Plant Life Form To Total Richnessmentioning
confidence: 81%
“…There are also examples of a uniform pattern of tree diversity that is independent of elevation or with little or no change in tree species richness with elevation change (Vázquez & Givnish, 1998; Martínez‐Camilo et al, 2018; Monge‐González et al, 2020). The diversity of shrubs, however, decreases slightly with elevation and increase with disturbance (Zhang et al, 2016; Bautista‐Bello et al, 2019), whereas climbers also seem to be more diverse at low elevations, but are associated with disturbed habitats (Dewalt et al, 2000; Bhattarai & Vetaas, 2003). By contrast, terrestrial herb diversity peaks at higher elevations and is usually higher in secondary vegetation (Gómez‐Díaz et al, 2017; but see Vázquez & Givnish, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Purpose: BIOVERA-Tree originated from the interdisciplinary research project BIOVERA, which aims at documenting and understanding biodiversity patterns along gradients of 2 altitude, climate, soil, and disturbance along an elevational transect at the Cofre de Perote in central Veracruz, Mexico (Carvajal-Hernández et al 2017, Gómez-Díaz et al 2017, Bautista-Bello et al 2019, Guzmán-Jacob et al 2020, Monge-González et al 2020. BIOVERA-Tree comprises forest plot data from eight elevational sites and three levels of forest-use intensity, namely old-growth, degraded, and secondary forests.…”
Section: General Descriptionmentioning
confidence: 99%